The effect of purple sweet potato boiled (ipomea batatas l. Poir) on increasing hb in 3rd trimester pregnant women - Pratiwi, Debby; Marlina, Marlina; Sembiring, Elya Rosa (Institute Of Computer Science (IOCS), 2024)
Purple sweet potato is a food ingredient that contains substances needed by pregnant women. The aim of the study was to determine the effect of giving purple sweet potato decoction to increasing HB in third trimester pregnant women at the Romauli Silalahi Clinic in 2023. The method used in this research was quasi-experimental using the One Group Pretest-Posttest Design. The population in this study as many as 40 TM III pregnant women. Sampling in this study was purposive sampling. Data analysis in this study was univariate and bivariate analysis using the Wilcoxon test. The results of the study were that respondents before being given the Purple Sweet Potato Stew Intervention on Increased HB Levels of TM III pregnant women at the Romauli Silalahi Clinic experienced a HB deficiency of 5 people (100%). Respondents After being given purple sweet potato stew, some TM III pregnant women at the Romauli Silalahi clinic had HB levels increased, 4 pregnant women with moderate HB levels (80%), 1 pregnant woman with mild HB levels (20%). There is an effect of boiling Purple Sweet Potato Stew on Increasing HB Levels in TM III Pregnant Women at the Romauli Silalahi Clinic with a p value of 0.002 <0.05. It is hoped that the results of this study will be used as material for evaluation and policy reference for health workers so that they can be applied and implemented by giving purple sweet potato stew to increase Hb in pregnant women so that anemia does not occur